Diffuse Primary Angiosarcoma of the Pleura: A Case Report and Review of the Literature. (2004) - Kurtz, Jean-Emmanuel; Serra, Sebastian; Duclos, Brigitte; Brolly, François; Dufour, Patrick; Bergerat, Jean-Pierre
Abstract : Primary pleural angiosarcoma is an extremely rare tumor. We report the case of a patient who presented with recurrent massive bilateral hemothoraxes. Although thoracoscopy was performed, biopsy samples of the pleura were inconclusive. The delayed onset of skin metastases led to the diagnosis of angiosarcoma, however the patient died from pleuropulmonary progression before treatment could be started. We review the literature of primary pleuropulmonary angiosarcoma and discuss its treatment modalities.